How to perform a root cause analysis for workup and future prevention of medical errors: a review. Issue 1 (December 2016) - Charles, Ryan; Hood, Brandon; Derosier, Joseph; Gosbee, John; Li, Ying; Caird, Michelle; Biermann, J.; Hake, Mark
Abstract Providing quality patient care is a basic tenant of medical and surgical practice. Multiple orthopaedic programs, including The Patient Safety Committee of the American Academy of Orthopaedic Surgeons (AAOS), have been implemented to measure quality of surgical care, as well as reduce the incidence of medical errors. Structured Root Cause Analysis (RCA) has become a recent area of interest and, if performed thoroughly, has been shown to reduce surgical errors across many subspecialties. There is a paucity of literature on how the process of a RCA can be effectively implemented. The current review was designed to provide a structured approach on how to conduct a formal root cause analysis. Utilization of this methodology may be effective in the prevention of medical errors.